2018
DOI: 10.1038/s41598-018-25494-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Enriched, Hadean Mantle Reservoir from 4.2-4.0 Ga zircon xenocrysts from Paleoarchean TTGs of the Singhbhum Craton, Eastern India

Abstract: Sensitive High-Resolution Ion Microprobe (SHRIMP) U-Pb analyses of zircons from Paleoarchean (~3.4 Ga) tonalite-gneiss called the Older Metamorphic Tonalitic Gneiss (OMTG) from the Champua area of the Singhbhum Craton, India, reveal 4.24-4.03 Ga xenocrystic zircons, suggesting that the OMTG records the hitherto unknown oldest precursor of Hadean age reported in India. Hf isotopic analyses of the Hadean xenocrysts yield unradiogenic 176Hf/177Hfinitial compositions (0.27995 ± 0.0009 to 0.28001 ± 0.0007; ɛHf[t] =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(33 citation statements)
references
References 83 publications
(108 reference statements)
1
32
0
Order By: Relevance
“…5). This implies the existence of a separate depleted reservoir during Paleoarchean which was probably complementary to the ancient enriched reservoir inferred by Chaudhuri et al (2018). Therefore, it appears that different sources contributed to different pulses of the OMTG.…”
Section: Granitoid Rocks In the Singhbhum Craton Older Metamorphic Tomentioning
confidence: 57%
See 4 more Smart Citations
“…5). This implies the existence of a separate depleted reservoir during Paleoarchean which was probably complementary to the ancient enriched reservoir inferred by Chaudhuri et al (2018). Therefore, it appears that different sources contributed to different pulses of the OMTG.…”
Section: Granitoid Rocks In the Singhbhum Craton Older Metamorphic Tomentioning
confidence: 57%
“…Other samples of the OMTG have negative ε Nd(t) value and are derived by melting of ancient crustal rocks or from a somewhat enriched mantle which were 150-450 million years older than the OMG amphibolite. Chaudhuri et al (2018) reported that the Eoarchean (~3.7 Ga) cores of zircons in the OMTG and the Paleoarchean (~3.6 to ~3.3) zircon grains in the OMTG have negative ε Hf(t) values of -4.7+1.4 to -6.6+1.1 and -0.4+1.2 to -3.7+1.8 respectively (Fig. 5).…”
Section: Granitoid Rocks In the Singhbhum Craton Older Metamorphic Tomentioning
confidence: 94%
See 3 more Smart Citations